Developing Core Capabilities for Local Health Departments to Engage in Land Use and Transportation Decision Making for Active Transportation. Issue 5 (September 2019) - Lemon, Stephenie C.; Goins, Karin Valentine; Sreedhara, Meera; Arcaya, Mariana; Aytur, Semra A.; Heinrich, Katie; Kerner, Bridget; Lyn, Rodney; Maddock, Jay E.; Riessman, Robin; Schmid, Thomas L.
Abstract : Objective: To develop a core set of capabilities and tasks for local health departments (LHDs) to engage in land use and transportation policy processes that promote active transportation. Design: We conducted a 3-phase modified Delphi study from 2015 to 2017. Setting: We recruited a multidisciplinary national expert panel for key informant interviews by telephone and completion of a 2-step online validation process. Participants: The panel consisted of 58 individuals with expertise in local transportation and policy processes, as well as experience in cross-sector collaboration with public health. Participants represented the disciplines of land use planning, transportation/public works, public health, municipal administration, and active transportation advocacy at the state and local levels. Main Outcome Measures: Key informant interviews elicited initial capabilities and tasks. An online survey solicited rankings of impact and feasibility for capabilities and ratings of importance for associated tasks. Feasibility rankings were used to categorize capabilities according to required resources. Results were presented via second online survey for final input. Results: Ten capabilities were categorized according to required resources. Fewest resources were as follows: (1) collaborate with public officials; (2) serve on land use or transportation board; and (3) review plans, policies, and projects. Moderate resources were as follows: (4) outreach to the community; (5) educate policy makers; (6) participate in plan and policy development; and (7) participate in project development and design review. Most resources were as follows: (8) participate in data and assessment activities; (9) fund dedicated staffing; and (10) provide funding support. Conclusions: These actionable capabilities can guide planning efforts for LHDs of all resource levels. Abstract : Supplemental Digital Content is Available in the Text.